Synthesis and comparison of the activities of a catalyst supported on two silicate materials - Vieira, Eduardo G. [UNESP]; Silva, Rafael O. [UNESP]; do Carmo, Devaney R. [UNESP]; Junior, Enes F. [UNESP]; Dias Filho, Newton L. [UNESP] (Elsevier, 2017)
The focus of this work is inspecting the synthesis and comparison of the activities of a catalyst supported on two silicate materials in the epoxidation of 1-octene. The two new catalyst materials were characterized by infrared spectroscopy, elemental analysis, solid-state 29Si and 13C nuclear magnetic resonance, scanning electronic microscope (SEM) and analysis of nitrogen. Lastly, the two new catalysts, Silsesq-TCA-[(W(CO)3I2)3] and Silica-TCA-[W(CO)3I2] were tested as catalysts in reactions of epoxidation of 1-octene and compared with their analogue not supported [W(CO)3I2(thiocarbamide)]. After an extensive literature search, we verified that our work is the first that has reported the immobilization process of [W(CO)3I2(NCCH3)2] on silsesquioxane and silica gel functionalized with propyl-thiocarbamide groups and their applications as catalysts of reactions of catalytic epoxidation of 1-octene.
Keywords: 1-Octene; Catalysts; Heterogeneous catalysts; Organometallic complex